Assessing The Effectiveness Of The 'Read With Miley' Program In Developing Reading Skills Among Chinese Children Teachers' Perspective/ تقييم فعالية برنامج 'اقرأ مع مايلي' في تنمية مهارة القراءة لدى الأطفال الصينيين من منظور المعلمين - Sedira, Amel; Abdullah, Nurazzelena; Che Haron, Sueraya; Mamat, Ariffin; Nawi, Amani; Yusup, Agung (Ijaz Arabi Journal of Arabic Learning, 2025)
With the growing interest in teaching Arabic to non-native, Chinese-speaking children—particularly in contexts related to religious and cultural identity—there is a critical need to evaluate innovative educational programs that address linguistic and cultural challenges. This study examines the effectiveness of the "Read with Miley" program in developing Arabic reading skills for this demographic, focusing on teachers' perspectives. Using a mixed-methods approach, the research combined a closed-ended questionnaire to gauge general perceptions with in-depth interviews to explore specific challenges and opportunities. The study sample consisted of five teachers who had fully and repeatedly implemented the program. Results indicated that the program successfully enhanced foundational skills, such as letter recognition and vowel reading, with strong approval for core materials, including the textbook. However, limitations were observed in using interactive digital tools, which hindered student engagement. Interviews revealed systemic and organizational challenges, highlighting the need for intensive teacher training on modern technologies and age-based class restructuring to optimize individualized interaction. Key recommendations include integrating AI-driven educational activities, fostering collaborations with digital design experts, and adopting flexible methodologies to accommodate learners’ linguistic and cultural diversity. These findings provide a practical framework for policymakers to refine Arabic language programs in non-Arabic-speaking environments.